2012
DOI: 10.1111/bjh.12172
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide efficacy in activated B‐cell‐like subtype diffuse large B‐cell lymphoma is dependent upon IRF4 and cereblon expression

Abstract: SummaryDurable responses with lenalidomide monotherapy have been reported in patients with non-Hodgkin lymphoma. In relapsed/refractory diffuse large B-cell lymphoma (DLBCL), higher responses were observed in the activated B-cell-like (ABC) subtype than in the germinal centre B-cell-like subtype. Herein, the molecular mechanisms involved in the differential efficacy of lenalidomide in DLBCL subtypes were investigated. Using DLBCL cell lines, lenalidomide treatment was found to preferentially suppress prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 45 publications
5
111
0
2
Order By: Relevance
“…This suggests that lenalidomide may be more effective when used as an early therapeutic option. Nevertheless, we confirmed that the advantage of lenalidomide treatment in non-GCB with respect to GCB is likely caused by the inhibitory activity of this immunomodulatory drug on the NF-kB pathway, which is aberrant in non-GCB [28]. In the present analysis, the drug dose (25 vs. 15 mg/day) significantly influenced the ORR, namely 51% vs. 21% (p 5 .002), mirroring the preclinical data on dosedependent pharmacokinetics [29].…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that lenalidomide may be more effective when used as an early therapeutic option. Nevertheless, we confirmed that the advantage of lenalidomide treatment in non-GCB with respect to GCB is likely caused by the inhibitory activity of this immunomodulatory drug on the NF-kB pathway, which is aberrant in non-GCB [28]. In the present analysis, the drug dose (25 vs. 15 mg/day) significantly influenced the ORR, namely 51% vs. 21% (p 5 .002), mirroring the preclinical data on dosedependent pharmacokinetics [29].…”
Section: Discussionsupporting
confidence: 84%
“…There were no differences in response rates, PFS and OS between the two groups. Lenalidomide can also target the ABC DLBCL by down regulating interferon regulatory factor (IRF4) and the NF-kB pathway [46]. Early clinical data showed preferential activity in refractory/relapsed ABC vs. GCB DLBCL, with an overall response rate (ORR) of 53% and 9%, respectively [47].…”
Section: Antiviral Therapy In Combination With Ebv Lytic Phase Inductionmentioning
confidence: 99%
“…IMiDs are now known to be effective against not only multiple myeloma and 5q− syndrome, but also diffuse large B-cell lymphoma (DLBCL), a type of non-Hodgkin lymphoma, as well as mantle cell lymphoma, and these effects are known to also depend on CRBN [37,38]. In addition, the development of CC-122 (Fig.…”
Section: Discussionmentioning
confidence: 99%